Competitividad de las pymes en el sector turismo de la ciudad de san José de Cúcuta - Angie Vannesa Sanjuán López; Claudia Alejandra Silva Franco; Marling Carolina Cordero Díaz (Mundo Fesc)
The central objective of this research is to determine the competitiveness factors of SMEs in the tourism sector in the city of San José de Cúcuta and its Metropolitan Area. It is based on the relationship between competitiveness and tourism; the study is quantitative and descriptive. The instruments used included interviews with two representatives of the Cotelco and the North Santander Mixed Promotion Corporation (Corporación Mixta de Promoción de Norte de Santander) trade associations, and a survey of business owners. The results indicate that the main factors affecting the sector's competitiveness are poor planning and a weak sense of belonging in the region, and, among other external factors, poor capacity to organize tourist attractions.